THE INFLUENCE OF WORKLOAD AND ADAPTATION ABILITY ON EMPLOYEE PERFORMANCE THROUGH SATISFACTION WORK AT PT. BANK OF SUMUT REGIONAL 1 MEDAN - Dwi Nurul Aisyah; Prihatin Lumbanraja; Parapat Gultom (RADJA PUBLIKA, 2023)
This study aims to analyze how workload, adaptability and job satisfaction can affect employee performance. The type of research used in this research is quantitative research. The population in this study were employees of PT Bank Sumut Regional 1 Medan with samples taken in this study were 170 respondents. The data used are primary data and secondary data obtained through a list of statements and documentation studies. The data analysis technique uses structural equation modeling (SEM) with the Smart PLS version 3.0 analysis tool. The results of the research directly show that workload has a positive and significant effect on employee performance, adaptability has a positive and significant effect on employee performance, workload has a negative and insignificant effect on job satisfaction, adaptability has a positive and significant effect on job satisfaction, and job satisfaction has a positive and significant effect on employee performance. Then the test is carried out indirectly resulting that the workload has a negative and insignificant effect on employee performance through job satisfaction and adaptability has a positive and significant effect on employee performance through job satisfaction.